2015
DOI: 10.1093/jxb/erv276
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen deficiency in barley (Hordeum vulgare) seedlings induces molecular and metabolic adjustments that trigger aphid resistance

Abstract: HighlightNitrogen deficiency induces extensive metabolic adjustment in barley leaves mediated largely by sugar signalling and receptor-like kinase cascades that overlap with biotic stress pathways to induce aphid resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 71 publications
1
42
0
Order By: Relevance
“…RNA from each of three replicates was hybridized to a custom‐design Agilent barley 60K microarray (Comadira et al . ). The microarray experimental design and dataset can be accessed at ArrayExpress (https://www.ebi.ac.uk/arrayexpress; accession # E‐MTAB‐5133).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…RNA from each of three replicates was hybridized to a custom‐design Agilent barley 60K microarray (Comadira et al . ). The microarray experimental design and dataset can be accessed at ArrayExpress (https://www.ebi.ac.uk/arrayexpress; accession # E‐MTAB‐5133).…”
Section: Methodsmentioning
confidence: 97%
“…RNA quality was assessed using the Agilent 2100 Bioanalyzer prior to microarray processing (Agilent Technologies, Santa Clara, CA, USA). RNA from each of three replicates was hybridized to a custom-design Agilent barley 60K microarray (Comadira et al 2015). The microarray experimental design and dataset can be accessed at ArrayExpress (https://www.ebi.ac.uk/arrayexpress; accession # E-MTAB-5133).…”
Section: Barley Transcriptome Analysesmentioning
confidence: 99%
“…Numerous studies have shown that high-level N fertilizer application to crops can influence plant-insect interactions, and potentially increase growth, food consumption, survival, reproductive rates and population densities of insect herbivores (Mattson, 1980; Moon et al, 1995; Brodbeck et al, 2001; Khan and Port, 2008). Conversely, a deficiency of N may alter plant metabolism and trigger insect resistance (Comadira et al, 2015). It has been demonstrated that the increasing populations of major insect pests of rice, including planthoppers, leaffolders, and stem borers, are closely related to the long-term excessive application of N fertilizers in most of the rice growing areas in Asia (Lu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Soluble fertilizer, mainly nitrogen, may also affect the susceptibility of plants to insect pests by altering the nutrient levels in plant tissue or tissue fractions. For example, nitrogen fertilizer increases free amino N in several crops [162]. This biochemical imbalance affects both herbivore damage and the ability of a plant to recover from herbivory [163].…”
Section: Tropical Environment and Conventional Versus Organic Agriculmentioning
confidence: 99%
“…The use of residues such as wood ash, biofertilizer, and powdered rocks may be another low cost alternative to increase soil fertility without affecting the imbalance of nutrients [162]. Biofertilizer consists of liquid fermented manure that can be produced at a local farm, and it has been identified as an alternative to chemical fertilizer to increase soil fertility and crop production in sustainable farming [163].…”
Section: Alternative Local Resources For Organic Soil Managementmentioning
confidence: 99%